Richter' s syndrome in patients with chronic lymphocytic leukemia - (:unkn) unknown (My University, 1999)
0

Objective: The development of a higher grade lymphoma in patients with chronic lymphocytic leukemia (CLL) is defined as Richter's syndrome (RS). The aim of this study was to analyze all CLL patients seen at Marmara University Hospital during 7 years of follow up in order to determine the incidence, clinical features and treatment outcome of patients who transformed to RS. Patients and Method: Fifty four patients with CLL were evaluated in this retrospective study, where records of all patients with CLL, who are followed up at the haematology out-patient clinics during 7 years, were examined in order to determine whether Richter transformation had occurred at any time during the course of the disease. Results: Richter's syndrome was observed in 3 out of 54 patient, giving an incidence of 5.6%. The presenting features of RS have been systemic symptoms, rapidly progressive lymphadenopathy, and elevation of lactate dehydrogenase LDH. None of the patients responded to systemic chemotherapy and the median survival was only 4 months following the diagnosis of RS. Conclusion: Early diagnosis of RS is possible with the recognition of the warning symptoms and signs, but treatment remains unsatisfactory. The study highlights the need to develop new strategies for the successful treatment of RS.
Keywords: Genel ve Dahili Tıp